Manajemen Perioperatif Pasien Insulinoma dengan Komorbid Epilepsi - Adiyanto, Bowo; Kurniawaty, Juni; Pambudi, Estu Agung (Jurnal Komplikasi Anestesi, 2020)
Insulinoma is a rare benign functional neuroendocrine in pancreas. Inappropriate secretion of insulin in patient with insulinoma results in hypoglycaemic episode with clinical symptoms. Meanwhile, epilepsy is a manifestation of brain disorder with a variety of clinical symptoms, cause by the release of electrical charges from brain neuron. We reported a 50 years old man with insulinoma which was planned for laparoscopic tumor resection. Patient also have epilepsy as a comorbid. The choice of anesthesia technique is intubation general anesthesia. Hypoglycemia is the main problem that can happen in preoperative and intraoperative period, so blood glucose was monitored every 30 minutes. Anesthesia consideration in this patient was avoiding hypoglycemia in preoperative and intraoperative period and avoiding proconvulsan anesthetic agent because the patient also have epilepsy as comorbid.